Pressure effects on superconductivity and structural parameters of ThFeAsN. (24th October 2018) - Wang, Honghong; Guo, Jing; Shao, Yeting; Wang, Cao; Cai, Shu; Wang, Zhe; Li, Xiaodong; Li, Yanchun; Cao, Guanghan; Wu, Qi; Sun, Liling
Abstract: Here we report effects of pressure on the recently discovered iron-based superconductor ThFeAsN, the first FeAs-based superconductor containing an actinide element, by in situ high-pressure resistance and synchrotron X-ray diffraction measurements. Our results show that the superconducting transition temperature ( T C ) decreases monotonously with increasing pressure and then vanishes at 25.4 GPa. The analysis of the As anion height above the Fe layer ( ), as well as the bond angle of As-Fe-As ( α ), for the pressurized ThFeAsN sample found that its T C vs. or α follows the same universal curve describing most of the iron-based superconductors. The results indicate that the lattice parameters also control the superconductivity of the ThFeAsN superconductor, similar to other FeAs-based superconductors, as long as the "superconducting gene" is a FeAs layer. Furthermore, we demonstrate that the ambient-pressure ThFeAsN is an "intrinsic" superconductor, while its lattice structure is not in the optimal state of the FeAs-based superconductors.